Awakening the "Walking Dead": Zombie Pedagogy for Millennials - Wadsworth, Nancy Dawn (Radical Teacher, 2017)
This article lays out the pedagogical benefits of using popular zombie productions, particularly AMC's The Walking Dead, to teach a critical introduction to modern political theory. Based on my undergraduate course: "Political Theory, Climate Change, and the Zombie Apocalypse," the article outlines how The Walking Dead can be used to critique the mythic assumptions built into modern social contract theory; to introduce other political ideologies, including conservatism, anarchism, fascism, and communism; and to consider the political challenges raised by a global problem such as climate change in an increasingly neoliberal environment. Zombie productions are offered as a particularly salient pedagogical tool that can help awaken critical political analysis for the Millennial Generation.